An integrated approach to maintaining cereal productivity under climate change - Reynolds, Matthew P.; Quilligan, Emma; Aggarwal, Pramod K.; Bansal, Kailash C.; Cavalieri, Anthony J.; Chapman, Scott C.; Chapotin, Saharah M.; Datta, Swapan K.; Duveiller, Etienne; Gill, Kulvinder S.; Jagadish, Krishna S.V.; Joshi, Arun Kumar; et al. (Elsevier, 2016)
Wheat, rice, maize, pearl millet, and sorghum provide over half of the world's food calories. To maintain global food security, with the added challenge of climate change, there is an increasing need to exploit existing genetic variability and develop cultivars with superior genetic yield potential and stress adaptation. The opportunity to share knowledge between crops and identify priority traits for future research can be exploited to increase breeding impacts and assist in identifying the genetic loci that control adaptation. A more internationally coordinated approach to crop phenotyping and modeling, combined with effective sharing of knowledge, facilities, and data, will boost the cost effectiveness and facilitate genetic gains of all staple crops, with likely spill over to more neglected crops.